HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis Is Not Associated with SNP rs12979860 of the IL-28B Gene - Ishak, Ricardo; Ishak, Marluísa de O. Guimarães; Feitosa, Rosimar Neris Martins; Azevedo, Vânia Nakauth; Sousa, Rita Catarina M.; Ferreira, Tuane C. S.; de Sá, Keyla Santos Guedes; Santana, Bárbara B.; Rosário Vallinoto, Antonio Carlos; Machado, Luiz Fernando A. (Mediators of Inflammation, 2015)
The present study investigated the association between the rs12979860 polymorphism in the IL-28B gene and HTLV-1 infection as well as the development of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). HTLV-1-infected patients (26 HAM/TSP symptomatic and 53 asymptomatic) and 300 seronegative healthy controls were investigated. Plasma levels of the cytokines TNF-α, TNF-β, IL-8, IL-10, IL-6, and IFN-γ from infected patients were measured using an indirect enzyme-linked immunosorbent assay. The HTLV proviral load was measured using a real-time PCR assay, and T-cell subset counts were determined by flow cytometry. Real-time PCR was used to genotype the rs12979860 SNP. The allelic and genotypic distributions displayed no significant differences among the investigated groups. No significant association between the serum cytokine levels and the presence of the rs12979860 SNP in symptomatic and asymptomatic subjects was observed. A positive correlation ( p = 0.0015 ) between TNF-β and IFN-γ was observed in the asymptomatic group, but a positive correlation was only observed ( p = 0.0180 ) between TNF-α and IL-6 in the HAM/TSP group. The proviral load was significantly higher in HAM/TSP patients than in asymptomatic subjects. The present results do not support a previous report indicating an association between the SNP rs12979860 and HAM/TSP outcome.